Walkability, Amenities, and Housing Choice in Downtown Madison - Barrett, Gabriella; Majid, Sadia; Carpenter, Sydney; Will, Thorbjorn (My University, 2018)
High-Rise apartments are a quintessential living option for residents in major cities and downtown areas. Two important aspects of high-rise apartments are the amenities that are offered and how walkable the area surrounding the apartment complex is. This study examines the Madison high-rise real estate market and investigates four high-rise apartment complexes: Hub Madison, Lucky Apartments, Galaxie Apartments, and The Constellation. The study analyzes what has led to the increase of high-rises in the Madison area, whether the amenities that are provided by developers align with what resident’s desire, and walkability throughout Madison. Research consisted of surveyed data of the four apartment complexes as well as interviews with key real estate and marketing executives. The research group calculated walk scores for the four apartment complexes, compared them to resident perceptions of walkability and walkscore.com scores and found a high degree of perceptual alignment. In addition, results suggest that personal amenities are more important than community amenities to housing choice, developers are aware of what amenities residents desire and use, and that the rental preferences of the millennial generation have enabled high-rise development.
Includes Bibliography, Appendices, Maps, Charts and Photographs. Fall 2017
Keywords: High-rise; Walkable; Amenities; Housing; Downtown; Madison